α-Enolase Lies Downstream of mTOR/HIF1α and Promotes Thyroid Carcinoma Progression by Regulating CST1 - Liu, Yang; Liao, Lida; An, Changming; Wang, Xiaolei; Li, Zhengjiang; Xu, Zhengang; Liu, Jie; Liu, Shaoyan (Frontiers in Cell and Developmental Biology, 2021)
Novel therapy strategies are crucial for thyroid cancer treatment. It is increasingly important to clarify the mechanism of thyroid cancer progression. Several studies demonstrate that α-Enolase (ENO1) participates in cancer development; nevertheless, the role of ENO1 in thyroid cancer progression remains unclear. In the present study, we found that the expression of ENO1 was upregulated in thyroid cancer samples. Proliferation and migration of thyroid cancer cells were suppressed by depletion of ENO1; conversely, ENO1 overexpression promoted thyroid cancer cell growth and invasion. To elucidate the mechanisms, we found that the hypoxia-related mTOR/HIF1 pathway regulated ENO1 expression. ENO1 regulated the expression of CST1; knockdown of CST1 reversed the tumorigenicity enhanced by ENO1 overexpression. Taken together, our findings provide a theoretical foundation for thyroid cancer treatment.